(untitled) (Journal of the College of Basic Education, 2023)
This study aims to investigate slogans as used by Arabs speakers duringrevolutions. It shows one of the important lexical features that characterizedslogans namely repetition as a narrative device which has been used for thepurpose of emphasis in respect to its various kinds .The study also classifiedslogans according to Quirk and Green (1973:191)classification of sentence withrelation to the direct speech act theory .The data is collected from the internet ,TV channels and newspapers .